2017
DOI: 10.1111/pim.12500
|View full text |Cite
|
Sign up to set email alerts
|

Th1/Th2 immune responses and oxidative stress in caprine flea allergy dermatitis

Abstract: Flea allergy dermatitis (FAD) is the common, often neglected skin disease of goats caused mainly by Ctenocephalides felis. This study aimed to evaluate the immuno-oxidative pathobiology of FAD in goats. Twelve goats from the same herd were divided into two groups of six animals each. The group I (FAD) included animals with natural flea infestation and severe dermatitis lesions. The group II (Healthy control) animals were free from any parasitic infestation. To assess the pathological changes, the markers of ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Eosinophils are involved in T helper 2 (Th2)-immune response in AD and Th2/Th22-dominant allergic responses, which are considered as the major molecular mechanism in AD. In addition, Th2 cytokines induce oxidative stress and severe inflammatory response, and lead to the aggravation of AD (49). Infiltration of eosinophils amplifies Th2-immune responses and Th2 cells begin secreting IL-4, IL-5 and IL-13, which augments skin inflammation (43,50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eosinophils are involved in T helper 2 (Th2)-immune response in AD and Th2/Th22-dominant allergic responses, which are considered as the major molecular mechanism in AD. In addition, Th2 cytokines induce oxidative stress and severe inflammatory response, and lead to the aggravation of AD (49). Infiltration of eosinophils amplifies Th2-immune responses and Th2 cells begin secreting IL-4, IL-5 and IL-13, which augments skin inflammation (43,50).…”
Section: Discussionmentioning
confidence: 99%
“…Infiltration of eosinophils amplifies Th2-immune responses and Th2 cells begin secreting IL-4, IL-5 and IL-13, which augments skin inflammation (43,50). A recent study (49) reported notable findings about AD; dupilumab, an anti-IL-4-receptor-α monoclonal antibody, can block signaling of IL-4 and IL-13, which are type 2/Th2 cytokines implicated in numerous allergic diseases, including AD. In this 1-year, randomized, double-blinded, placebo-controlled, phase 3 trial, signs and symptoms of patients with AD were alleviated by dupilumab with acceptable safety.…”
Section: Discussionmentioning
confidence: 99%
“…Animals, plants, and microorganisms are all exposed to a broad range of environmental stresses, leading to the development of a wide variety of stress responses and adaptations . Responses include changes in gene expression, as well as morphological and physiological changes . A wide variety of adaptations have evolved, as they impact the survival and distribution of species .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Responses include changes in gene expression, as well as morphological and physiological changes. [4][5][6] A wide variety of adaptations have evolved, as they impact the survival and distribution of species. 7,8 For example, in response to diverse genotoxic stresses, such as ionizing and ultraviolet (UV) radiation, oxidative stress, and chemotherapeutic agents, the genotoxic stress response system is activated to repair DNA damage; in the case of irreparable damage, apoptosis is induced in favor of organismal survival.…”
Section: Introductionmentioning
confidence: 99%
“…(b) Polyphenols increase the growth of probiotics: Bifidobacterium and Lactobacillus, known to have beneficial impacts in food allergies. (c) By targeting the pathogenesis of allergy [226][227][228][229][230][231][232][233], the effective polyphenolic anti-oxidative stress (please refer to 3.1 (1) to (6) & 4.1) readily eases allergic asthma, atopic dermatitis, and beyond.…”
Section: Anti-allergymentioning
confidence: 99%